Radix Actinidia chinensis Suppresses Renal Cell Carcinoma Progression: Network Pharmacology Prediction and In Vivo Experimental Validation - Biao Liu; Liang Zhang (Analytical Cellular Pathology)
Background. Renal cell carcinoma (RCC) is a frequent disease with limited curative methods. This study is aimed at investigating the role and mechanism of Radix Actinidia chinensis (RAC) on RCC. Methods. The ingredients, target, and crucial pathways of RAC in RCC therapy were analyzed by network pharmacology. Then, an RCC animal model was established by subcutaneously injecting A498 cell suspension to BALB/c nude mice. After 1 week, the mice in the RAC-L/M/H groups were administered with RAC at 5, 10, and 20 mg/kg/d, respectively. The histopathology of the tumor was evaluated. The contents of tumor inflammatory cytokines and serum oxidative stress factors were detected by ELISA. The apoptosis of tumor tissues was assessed by TUNEL staining. The expressions of apoptosis-, proliferate-, autophagy-, and MAPK-related proteins were measured. Results. There were 13 active ingredients, and 20 RCC-relevant targets were selected from RAC; KEGG pathway indicated that these targets were enriched in the PI3K/AKT/mTOR and MAPK pathway. In in vivo experiments, RAC not only obviously damaged tumor cells and decreased the release of inflammatory cytokines and oxidative stress factors but also enhanced the apoptosis of the tumor cell in RCC mice. Besides, the expressions of apoptosis-, proliferate-, autophagy-, PI3K/AKT/mTOR path-, and MAPK path-related proteins were all affected by RAC. Conclusion. RAC attenuated RCC by regulating inflammation response, oxidative stress, apoptosis, proliferation, and autophagy, and its effects were partly linked to the PI3K/AKT/mTOR and MAPK pathway, which indicated that RAC may be a candidate drug for RCC.